ТHE DEVELOPMENT OF THE TECHNICAL EDUCATION IN NEFU - Terentiy A. Kornilov; Ekaterina A. Arkhangelskaya (Высшее образование в России, 2016)
The article dwells on the role of engineering education in the innovative development of the North-East of the country. The basic principles of advanced technical education and the ways of their implementation are presented. First of all it is necessary to ensure interdisciplinarity and polydisciplinarity of research activities, the rational combination of research, project and entrepreneurial activities. Secondly, the university should develop the real mechanisms of interaction with business, industry and research institutes on the basis of state-private partnership and create the regional engineering clusters with the experimental grounds for testing of innovation technologies in northeast climate conditions. The third principle implies optimization of students’ self-dependent work including participation of students in team project activities with the attraction of employers and practical experts.